2021
DOI: 10.3389/fped.2021.667247
|View full text |Cite
|
Sign up to set email alerts
|

Possible Hepatoprotective Effect of Tocotrienol-Rich Fraction Vitamin E in Non-alcoholic Fatty Liver Disease in Obese Children and Adolescents

Abstract: Obesity has become a worldwide health concern among the pediatric population. The prevalence of non-alcoholic fatty liver disease (NAFLD) is growing rapidly, alongside the high prevalence of obesity. NAFLD refers to a multifactorial disorder that includes simple steatosis to non-alcoholic steatohepatitis (NASH) with or devoid of fibrosis. NAFLD is regarded as a systemic disorder that influences glucose, lipid, and energy metabolism with hepatic manifestations. A sedentary lifestyle and poor choice of food rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 124 publications
(153 reference statements)
0
8
0
Order By: Relevance
“…In a study done on 120 school students aged between 15 and 18 years old, high serum levels of α- and γ-tocopherol elicited an enhancement in the academic performance and students’ physical activity [ 172 ]. In addition, vitamin E could play a role in the adolescence age that leads to better prognosis in cases of non-alcoholic fatty liver disease (NAFLD) [ 173 ]. Studies have revealed that adolescent patients with NAFLD could show moderate improvement in liver biomarkers and histology when treated by tocotrienol form of vitamin E (Fig.…”
Section: Vitamin Ementioning
confidence: 99%
See 1 more Smart Citation
“…In a study done on 120 school students aged between 15 and 18 years old, high serum levels of α- and γ-tocopherol elicited an enhancement in the academic performance and students’ physical activity [ 172 ]. In addition, vitamin E could play a role in the adolescence age that leads to better prognosis in cases of non-alcoholic fatty liver disease (NAFLD) [ 173 ]. Studies have revealed that adolescent patients with NAFLD could show moderate improvement in liver biomarkers and histology when treated by tocotrienol form of vitamin E (Fig.…”
Section: Vitamin Ementioning
confidence: 99%
“…Studies have revealed that adolescent patients with NAFLD could show moderate improvement in liver biomarkers and histology when treated by tocotrienol form of vitamin E (Fig. 5 ) [ 173 ].…”
Section: Vitamin Ementioning
confidence: 99%
“…8 The statin therapy commonly use all over the world for the management of dyslipidemia 9 Vitamin E is one of the fat soluble, essential vitamin because it cannot synthesize inside the human body. It is natural antioxidant due to its antioxidant property it consider as cardio protective as well as hepatic protective agent 10,11 . Vitamin E consider as cardio protective agent because it lowers the serum cholesterol level, LDL level as well.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin E consider as cardio protective agent because it lowers the serum cholesterol level, LDL level as well. 11 The active component of vitamin E, alpha tocopherol and tocotrienol inhibiting the cholesterol synthesis by post-transcriptional suppression of regulatory enzyme of cholesterol metabolism i.e HMG CoA Reductase 12,13 . Vitamin E also suppressesthe lipid peroxidation process by inhibiting the protein kinase C and phospholipase A2.…”
Section: Introductionmentioning
confidence: 99%
“…Currently available treatments with demonstrated benefits against NAFLD include lipid-lowering agents (statins), insulin-sensitizing agents (e.g., pioglitazone), apical sodium-dependent bile acid transporter (ASBT) inhibitors, and antioxidants (e.g., vitamin E) ( Cusi et al, 2016 ; Ge et al, 2019 ; Al-Baiaty et al, 2021 ; Lee et al, 2021 ). None of these treatments have been approved by the US Food and Drug Administration due to limited effectiveness and adverse effects ( Rao et al, 2020 ; Pafili and Roden, 2021 ; Boeckmans et al, 2019 ; Caparros-Martin et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%